Vascular anatomy of kiwi fruit and its implications for the origin of carpels - Guo, Xue-Min; Xiao, Xiao; Wang, Gui-Xi; Gao, Rong-Fu (Frontiers in Plant Science, 2013)
Kiwi fruit is of great agricultural, botanical, and economic interest. The flower of kiwi fruit has axile placentation, which is typical for Actinidiaceae. Axile placentation is thought derived through fusion of conduplicate carpels with marginal placentation according to the traditional doctrine. Recent progress in angiosperm systematics has refuted this traditional doctrine and placed ANITA clade rather than Magnoliaceae as the basalmost clade. However, the former traditional doctrine stays in the classrooms as the only teachable theory for the origin of carpels. To test the validity of this doctrine, we performed anatomical study on kiwi fruit. Our study indicates that the placenta has a vascular system independent of that of the ovary wall, the ovules/seeds are attached to the placenta that is a continuation of floral axis enclosed by the lateral appendages that constitute the ovary wall, and there are some amphicribral bundles in the center of placenta and numerous amphicribral bundles supplying ovules/seeds in kiwi fruit. The amphicribral vascular bundles supplying the ovules/seeds are comparable to those usually seen in branches, but not comparable to those seen in leaves or their derivatives. This comparison indicates that the placenta in kiwi fruit cannot be derived from the fusion of collateral ventral bundles of conduplicate carpels, as suggested by traditional doctrine. Instead the vascular organization in placenta of kiwi suggests that the placenta is a shoot apex bearing ovules/seeds laterally. This conclusion is in line with the recently raised Unifying Theory, in which the placenta is taken as an ovule-bearing branch independent of the ovary wall (carpel in strict sense). Similar vascular organization in placenta has been seen in numerous isolated taxa besides kiwi fruit. Therefore whether such a pattern is applicable for other angiosperms is an interesting question awaiting answering.